An Analysis of Medical Care Services for Children With Rare Diseases in the Russian Federation - Volgina, Svetlana Ya.; Sokolov, Alexey A. (Frontiers in Pharmacology, 2021)
Rare diseases continue to present numerous challenges for the medical field worldwide. Understanding innovative mechanisms of service provision for patients with rare conditions through shared communication across different healthcare systems should be encouraged. This study presents the organization of medical care for people with rare diseases in Russia, while also exploring the epidemiology of both life-threatening and chronic, progressive, rare diseases. Further, the regulation of medical care provision is examined, including the preferential provision of medicines in different Russian regions and potential role of compulsory medical insurance. The principles guiding patient referrals to appropriate specialist centres for rare diseases are outlined, including considering the increased role that public-patient organizations have in developing healthcare systems. In reviewing the specialized resources available for patients with rare diseases, medical genetics services offering diagnostics and counselling are discussed. Additionally, population-level preventive care necessitates significant investment, principally in diagnostic technology and screening programs. As seen elsewhere, these initiatives involve forming reference centres and tertiary-level pediatric departments staffed by multidisciplinary specialists in rare diseases. Numerous challenges are highlighted relating to Russian healthcare systems, including the financing of expensive treatments and ensuring equitable access to medical care for those patients with rare diseases outside of State-subsidized programs. Recommendations are made on creating international registries for knowledge sharing, quality appraisal, newborn screening, diagnostic challenges, available treatments and rehabilitation services. Given the high cost of rare diseases, cost-effective interventions are advisable, particularly developing preventive programs and targeting the most common and severe mutations in patients planning pregnancies.